BEYOND BORDERS: EXPLORING THE ROLE OF FOREIGN OWNERSHIP IN CORPORATE CASH HOLDINGS? - Firmansyah, Amrie; Kartiko, Nafis Dwi; Arham, Amardianto (JRAK, 2025)
High cash holdings in Indonesian banking firms raise concerns regarding efficiency and optimal resource allocation. This study investigates the impact of foreign ownership on cash holdings in Indonesian banks. This study is based on 637 firm-year observations from 46 Indonesian banks covering the 2004–2022 period. Due to incomplete yearly data, the analysis applies Ordinary Least Squares (OLS) regression using a cross-sectional approach. The results show that foreign ownership negatively affects all cash-holding proxies, particularly in mature banks with large asset bases. In contrast, it increases cash holdings in young banks with large assets and mature banks with small assets. These findings suggest that foreign investors may influence more efficient cash allocation, encouraging banks to direct resources toward productive investments. The study offers practical implications for policymakers and banking practitioners in enhancing cash management and governance structures in the presence of foreign stakeholders.